2018
DOI: 10.1016/j.cnur.2017.10.010
|View full text |Cite
|
Sign up to set email alerts
|

End-of-Life Care and Bereavement Issues in Human Immunodeficiency Virus–AIDS

Abstract: This review article addresses end-of-life care issues characterizing human immunodeficiency virus progression by delineating associated stages of medical and nursing care. The initial progression from primary medical and nursing care aimed at functional cure to palliative care is discussed. This transition is considered in accord with the major symptoms experienced, including fatigue, pain, insomnia; decreased libido, hypogonadism, memory, and concentration; depression; and distorted body image. From the stage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
62
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(63 citation statements)
references
References 43 publications
1
62
0
Order By: Relevance
“…Engagement efforts and preliminary acceptability research in Southern California revealed that EOL HIV cure-related research is widely accepted in the local community [ 19 ]. This is likely because many older adults living with HIV have survived an epidemic that was once untreatable [ 3 ]. Similarly, cancer research has benefited from peri-mortem and rapid autopsy research programs, providing a better understanding of cancer mechanisms and how various oncology drugs have affected these cellular mechanisms [ 16 , 20 ].…”
Section: The Last Gift Studymentioning
confidence: 99%
See 4 more Smart Citations
“…Engagement efforts and preliminary acceptability research in Southern California revealed that EOL HIV cure-related research is widely accepted in the local community [ 19 ]. This is likely because many older adults living with HIV have survived an epidemic that was once untreatable [ 3 ]. Similarly, cancer research has benefited from peri-mortem and rapid autopsy research programs, providing a better understanding of cancer mechanisms and how various oncology drugs have affected these cellular mechanisms [ 16 , 20 ].…”
Section: The Last Gift Studymentioning
confidence: 99%
“…While the notion of EOL clinical research is not in itself ethically problematic, it can be difficult to conduct such research well given the inherent practical and logistical challenges [ 30 , 31 ]. For instance, EOL research occurs at the same time as participants and their loved ones prepare for death [ 3 ]. More specific to the Last Gift study, one methodological issue that arises is the uncertainty associated with the EOL prognosis [ 32 ].…”
Section: Ethical Principles For Clinical Research At the Eolmentioning
confidence: 99%
See 3 more Smart Citations